The Protection of Online Shopping Consumer Rights in Australia - Muhammad Syuib (Jurnal Justisia : Jurnal Ilmu Hukum, Perundang-undangan dan Pranata Sosial, 2020)
As one of the advanced countries in the world, Australia is putting technology as main instrument in dealing with daily activity, included in shopping. Therefore, nowadasys, many Australian rely on online shopping. It seems everything becomes easier when it is dealt online. People do not need to go outside their home and spend their money. What they can merely need is just sit at home and wait for the order. Thus, online shopping can be argued is more effective and efficient in this era. However, beyond this positive aspect, there are also some negative aspects. Among them is the quality of the product. Buyers (consumers) would never see goods or services directly. They only view the products or services through pictures or videos which are available on the website. The problem is, these images and videos might not be as good as reality. The vendors post the high quality pictures and videos on the site merely to attract consumers. Another issue is, difficult to communicate with the seller after buying the product. During the negotiation, it is easy to contact seller, but after the products are sold, majority vendors would “disappear”. Security payment is among on the risk list as well. Therefore, it is interesting to be researched, how the Australian law then protects its society from such risk. The Government claims that the Australian Competition and Consumer (ACC) Act 2010 has become law umbrella in protecting Australian in dealing with online shopping.